2017
DOI: 10.1056/nejmoa1708337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sotagliflozin Added to Insulin in Patients with Type 1 Diabetes

Abstract: Among patients with type 1 diabetes who were receiving insulin, the proportion of patients who achieved a glycated hemoglobin level lower than 7.0% with no severe hypoglycemia or diabetic ketoacidosis was larger in the group that received sotagliflozin than in the placebo group. However, the rate of diabetic ketoacidosis was higher in the sotagliflozin group. (Funded by Lexicon Pharmaceuticals; inTandem3 ClinicalTrials.gov number, NCT02531035 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
369
2
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 346 publications
(400 citation statements)
references
References 34 publications
22
369
2
7
Order By: Relevance
“…In the sotagliflozin group, 28.6% of patients met the primary end point versus 15.2% of patients in the placebo group. Moreover, the patients in the sotagliflozin group achieved a significantly lower HbA1c, systolic blood pressure and body weight and required significantly less daily insulin compared to the placebo group [18]. The efficacy results of these three main trials are summarized in Table 2.…”
Section: Use Of Sglt2 Inhibitors In Type 1 Diabetic Patients: Effectsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the sotagliflozin group, 28.6% of patients met the primary end point versus 15.2% of patients in the placebo group. Moreover, the patients in the sotagliflozin group achieved a significantly lower HbA1c, systolic blood pressure and body weight and required significantly less daily insulin compared to the placebo group [18]. The efficacy results of these three main trials are summarized in Table 2.…”
Section: Use Of Sglt2 Inhibitors In Type 1 Diabetic Patients: Effectsmentioning
confidence: 99%
“…As stated previously, intestinal SGLT1 inhibition can cause diarrhea. The inTandem trial showed that twice as many patients reporting diarrhea were in the sotagliflozin group compared to the placebo group [18]; however, overall this risk seemed lower than expected indicating a potential therapeutic window. After reabsorption into the systemic circulation, sotagliflozin will inhibit SGLT2 in the kidney.…”
Section: Use Of Sglt2 Inhibitors In Type 1 Diabetic Patients: Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the inTANDEM study, addition of sotagliflozin (400 mg) for 24 weeks reduced HbA1c (p<0.0001); the incidence of severe hypoglycaemia was similar in the treated (3%) and placebo (2.4%) groups and diabetic ketoacidosis occurred in 3% of patients receiving sotagliflozin and 0.4% of patients in the placebo group. 27,28 Anything else? The Messe Berlin (aka Berlin ExpoCenter City), Messedamm 22, will host EASD 2018.…”
Section: … Newer Agentsmentioning
confidence: 99%